Improving electronic payment system controls to reduce theft and fraud in merchandise marketing - F .Mustafa, Rasha (International Journal of Psychosocial Rehabilitation, 2020)
The development of telecommunications has led to the fact that nowadays individuals and companies around the world are connected with each other through electronic communication channels.The Internet, being a tool for organizing a single information space, has allowed businesses to enter a new stage of development; on the one hand, it provided manufacturers with access to a maximum audience of consumers with all their varied preferences; on the other hand, it gave customers the opportunity to enter their orders into a well-functioning production management system using electronic interfaces. Thus, in recent years, e-business and e-commerce have entered the lives of large and small firms as well as individuals.Business is an entrepreneurial activity aimed at the systematic receipt of profit from the use of property, the sale of goods, the performance of work, or the provision of services and carried out by subjects at their own risk and under their responsibility in accordance with applicable law.Electronic business (e-business) is a business that uses the capabilities of global information systems. In other words, this is a form of doing business in which a significant part of it is carried out using information technology. As the main components of e-business, it is customary to distinguish the internal organization of the company on the basis of a single information network (intranet) and external interaction with partners, suppliers, and customers through extranet networks and the Internet. The main goal of creating an intranet (local area network) is to increase the efficiency of employee interaction and optimize company management processes.